Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/srep16349
|View full text |Cite
|
Sign up to set email alerts
|

Lignosus rhinocerotis (Cooke) Ryvarden mimics the neuritogenic activity of nerve growth factor via MEK/ERK1/2 signaling pathway in PC-12 cells

Abstract: The traditional application of the sclerotium of Lignosus rhinocerotis (tiger’s milk mushroom) by the indigenous folks as tonic and remedy to treat a variety of ailments has been documented in Malaysia. Indigenous communities claimed to have consumed the decoction to boost their alertness during hunting. Mental alertness is believed to be related to neuronal health and neuroactivity. In the present study, the cell viability and neuritogenic effects of L. rhinocerotis sclerotium hot aqueous and ethanolic extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 54 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…According to the studies by Seow et al ( 2013a , 2015 ), the maximal neuritogenic activity in PC12 at 25 μg/mL of aqueous extract was 20.99% followed by ethanolic extract (17.4%) and crude polysaccharides (16.4%). The hot aqueous extract (25 μg/mL) stimulated neuritogenesis as equivalent to NGF (50 μg/mL).…”
Section: Description Of L Rhinocerotismentioning
confidence: 97%
See 2 more Smart Citations
“…According to the studies by Seow et al ( 2013a , 2015 ), the maximal neuritogenic activity in PC12 at 25 μg/mL of aqueous extract was 20.99% followed by ethanolic extract (17.4%) and crude polysaccharides (16.4%). The hot aqueous extract (25 μg/mL) stimulated neuritogenesis as equivalent to NGF (50 μg/mL).…”
Section: Description Of L Rhinocerotismentioning
confidence: 97%
“…On the other hand, the ethyl acetate and n-butanol fractions of L. rhinocerotis were found to mimic the neuritogenic activity of NGF by targeting the TrkA receptor and activated the mammalian target of rapamycin (mTOR) signaling pathway with the phosphorylation of the transcription factors, cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB), and leading to the increased expressions of neuritogenesis biomarker, i.e., the growth associated protein 43 (GAP43), tubulin alpha 4A (TUBA4A), and tubulin beta 1 (TUBB1) in PC12 cells (Seow, 2016 ).…”
Section: Description Of L Rhinocerotismentioning
confidence: 99%
See 1 more Smart Citation
“…Although U0126 is frequently used as an ERK1/2 inhibitor, its actual target is mitogen-activated and extracellular signal-regulated kinase 1/2 (MEK1/2), simply because MEK1/2-ERK1/2 is generally considered an integrated signal pathway [26] , [27] , while SCH772984 is a direct inhibitor to ERK1/2. To confirm the involvement of MEK1/2 in HBO induced HSP32 expression, the activation of MEK1/2 at 0, 0.5, 1, 2 and 4 h following HBO exposure and the effects of another MEK1/2 inhibitor trametinib or MEK1/2 knockdown were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The existing data showed that activation of ERK1/2 played a mostly positive role in the regulation of HSP32 [25] , [39] , and ERK1/2 is the only known physiological substrates of MEK1/2 [26] . U0126 is a specific inhibitor of MEK1/2 and is commonly used to inhibit the activation of the MEK1/2-ERK1/2 cascade [27] , [40] . As far as we know, this is the first finding that MEK1/2 may work via pathways other than ERK1/2.…”
Section: Discussionmentioning
confidence: 99%